Ethics and Integrity in the Context of Economic Research Within Doctoral Schools - Vasile Dinu; Veronica Câmpian; Cristinel Vasiliu; Laurențiu Tăchiciu; Dan-Cristian Dabija (Amfiteatru Economic)
Nationally and internationally, there is an upward trend in terms of ethics and integrity in scientific research. Yet, there are many opinions, both in academia and in society, about the many cases of violations of ethical principles in research. This requires today more than ever that the observance of ethics in research to become an increasingly important and relevant desideratum in the contemporary society. Failure to achieve this requirement can generate serious consequences on university education, especially in the long term, materialized by a series of consequences such as: the decrease in the quality of academic activity; devaluation of the status of university professors; undervaluation of scientific research; underappreciation of doctoral studies; lack of respect at the level of the society. Therefore, the members of the academic community – students, master students, PhD students and professors – must become increasingly aware of the social effects of noncompliance with the principles of ethics and integrity in scientific research. The purpose of this research is aimed at evaluating the perception of PhD students and doctoral supervisors on the observance of the principles of ethics in the research activity within the doctoral schools in economic sciences, as well as the identification of the most important factors with significant influence on ethics and integrity in research. In this regard, the authors of the present paper have carried out quantitative research among the two target groups within the doctoral schools of economic sciences affiliated with the Universitaria Consortium in Romania, respectively, PhD students and doctoral supervisors. The data collected from the 455 respondents (169 PhD supervisors and 286 PhD students) were analyzed using structural equation modeling in SmartPLS. The conceptual model proposed by the authors reveals that the observance of ethics in scientific research is based on professionalism, honesty, academic freedom, integrity, ethical behavior, and the avoidance of violation of ethical principles. The originality of the paper consists in the realization of structural models that highlight the most influential factors in the observance of ethics and integrity in economic research, but also of the relations between them, as well as the differences and similarities between PhD students and doctoral supervisors regarding their perception of ethics and integrity in research. By knowing these factors, academic programs can be initiated that will lead to a higher level of academic integrity in doctoral schools and better results in observing the ethics in scientific research, but also in the training of future researchers in the field of economic sciences.